The development of homozygous maize lines using an in vivo haploid induction in the Croatian germplasm - Mazur, Maja (Array, 2019)
The in vivo haploid induction has been widely applied to the maize breeding in recent decades, but it has not been used in the breeding programs in the Republic of Croatia by now. This study's objectives were to examine the haploid induction rates in the Croatian germplasm and to evaluate the properties of the D0 haploids, which are essential for a successful implementation of this method in breeding. The in vivo haploid induction was performed on 11 single-cross hybrids using the Zarodyshevy Marker Krasnodarsky (ZMK) inducer, and colchicine was used as a chromosome doubling agent. Emergence, misclassification rate, colchicine treatment survival, chromosome doubling rate and self-pollination success were examined in the D0 generation. The haploid induction rates ranged from 6.9 to 15.8%, which is consistent with the average induction rates characteristic of the ZMK inducer and the other modern ones. Significant differences were found among the populations of D0 haploids for all tested properties, except for self-pollination success. On average, the misclassification rates were lower, and the seedling survival rates were higher than those reported in other studies, indicating a possibility of a successful application of the doubled haploid method in maize breeding.